An atypical mating system in a neotropical manakin - Gaiotti, Milene G. (R Soc Open Sci, 2020)
Most of the diversity in the mating systems of birds and other animals comes at higher taxonomic levels, such as across orders. Although divergent selective pressures should lead to animal mating systems that diverge sharply from those of close relatives, opportunities to examine the importance of such processes are scarce. We addressed this issue using the Araripe manakin (Antilophia bokermanni), a species endemic to a forest enclave surrounded by xeric shrublands in Brazil. Most manakins exhibit polygynous lekking mating systems that lack territoriality but exhibit strong sexual selection. In sharp contrast, we found that male Araripe manakins defended exclusive territories, and females nested within male territories. However, territoriality and offspring paternity were dissociated: males sired only 7% of nestlings from the nests within their territories and non-territorial males sired numerous nestlings. Moreover, female polyandry was widespread, with most broods exhibiting mixed paternity. Apparently, territories in this species function differently from both lekking arenas and resource-based territories of socially monogamous species. The unexpected territoriality of Araripe manakins and its dissociation from paternity is a unique evolutionary development within the manakin clade. Collectively, our findings underscore how divergences in mating systems might evolve based on selective pressures from novel environmental contexts.